2019
DOI: 10.3201/eid2502.181246
|View full text |Cite
|
Sign up to set email alerts
|

Bat Influenza A(HL18NL11) Virus in Fruit Bats, Brazil

Abstract: Screening of 533 bats for influenza A viruses showed subtype HL18NL11 in intestines of 2 great fruit-eating bats (Artibeus lituratus). High concentrations suggested fecal shedding. Genomic characterizations revealed conservation of viral genes across different host species, countries, and sampling years, suggesting a conserved cellular receptor and wide-ranging occurrence of bat influenza A viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 15 publications
2
35
0
3
Order By: Relevance
“…Surveillance studies in two different species of fruit bats, the little yellow-shouldered bat (Sturnira lilium) in Guatemala and the flatfaced fruit-eating bat (Artibeus jamaicensis) in Peru, led to the characterization of type A-like influenza viruses, H17N10 and H18N11, respectively (Tong et al 2012(Tong et al , 2013. More recently, surveillance studies in Egypt revealed the presence of another bat virus, more similar to avian-origin influenza virus strains than those previously characterized in Central and South America (Tong et al 2012;Campos et al 2019;Kandeil et al 2019). The Egyptian fruit bat (Rousettus aegyptiacus) virus isolates contain an HA segment with common ancestry with other H9 viruses, and low-level cross-reactivity with serum raised against H9N2 viruses (Kandeil et al 2019).…”
Section: H9-like Viruses In Fruit Batsmentioning
confidence: 99%
“…Surveillance studies in two different species of fruit bats, the little yellow-shouldered bat (Sturnira lilium) in Guatemala and the flatfaced fruit-eating bat (Artibeus jamaicensis) in Peru, led to the characterization of type A-like influenza viruses, H17N10 and H18N11, respectively (Tong et al 2012(Tong et al , 2013. More recently, surveillance studies in Egypt revealed the presence of another bat virus, more similar to avian-origin influenza virus strains than those previously characterized in Central and South America (Tong et al 2012;Campos et al 2019;Kandeil et al 2019). The Egyptian fruit bat (Rousettus aegyptiacus) virus isolates contain an HA segment with common ancestry with other H9 viruses, and low-level cross-reactivity with serum raised against H9N2 viruses (Kandeil et al 2019).…”
Section: H9-like Viruses In Fruit Batsmentioning
confidence: 99%
“…As a consequence, IAVs are exposed to recurrent selective pressures, leading to a range of virus variants that are able to cope with the new host environment [1]. Bats were not considered to be part of this IAV habitat until recently, when two phylogenetically distinct IAV lineages, designated H17N10 and H18N11, were identified in the New World bats Sturnira lilium and Artibeus spp, respectively [2][3][4]. Likewise, Old World bats can harbor influenza viruses, as exemplified by the genetically distinct H9N2 virus found in Egyptian fruit bats (Rousettus aegyptiacus) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the lack of transmission could also be attributed to an Artibeus species specificity of H18N11. Although various South American fruit bat species have been found seropositive for H17 and H18 [9], until now full H18N11 genomic sequences or infectious viruses have been only isolated from Artibeus planirostris and Artibeus lituratus or Artibeus jamaicensis, respectively [9,18,31]. Considering this, it is tempting to speculate that species-specific differences in the immunity or the adaptation of H18 to MHC-II molecules of Artibeus spp.…”
Section: Discussionmentioning
confidence: 99%